Brain 3D-echographic early predictors of neuro-behavioral disorders in infants: a prospective observational study. (16th February 2022) - Aisa, Maria Cristina; Barbati, Antonella; Gerli, Sandro; Clerici, Graziano; Nikolova, Natasha; Giardina, Irene; Babucci, Giulia; De Rosa, Francesca; Cappuccini, Benito
Abstract: Background: Prematurity, low birth weight (LBW), very low birth weight (VLBW), and intrauterine growth restriction (IUGR) are risk factors of long-term poor neuro-development outcomes and associate with reduction of regional brain volumes. Objective: To evaluate the possible role of 3D ultrasound sonography (3DUS) regional brain volumes, measured at 30–40 days of postnatal period, as early predictors of long-term risk of neuro-behavioral disorders. Methods: A highly selected population, which included: full-term, preterm, IUGR, and preterm-IUGR born individuals, was followed longitudinally from 30 to 40 days of postnatal period to the second year of life. The population was mostly composed of bichorionic twins to ensure a, theoretically, major intracategory homogeneity. Preterm and IUGR subjects were characterized by a gestational age (GA) and birth weight (BW)>32 weeks and >1500 g, respectively, whereas the full-term neonates were of 37 weeks GA. At enrollment, the assessment of the volumetric measurements was performed using the 3DUS. The evaluation of neuro-development was performed at 2 years using the Griffiths Mental Development Scales. Results: The 3DUS measurements of whole brain, thalamus, frontal cortex, and cerebellum volumes, assessed at 30–40 days of postnatal period, were significantly reduced in infants characterized by negative outcome. In addition, the respective areas of the ROC curves, made by comparing values of normal and abnormal neuro-development groups, were indicative of a strong diagnostic accuracy. Conclusion: Data found suggest that the 3DUS regional brain volumes may assume a significant role as early indicators of neonates at major risk of neuro-behavioral disorders in later life. Further and larger studies in this direction are needed to validate this significant perspective.